Drug Abuse as a Predictor of Rearrest or Failure to Appear in Court in New York City, 1984 - Wish, Eric D. ([Verlag nicht ermittelbar], 1993)
This data collection was undertaken to estimate the prevalence of drug use/drug use trends among booked arrestees in New York City and to analyze the relationship between drug use and crime. The data, which were collected over a six-month period, were generated from volunteer interviews with male arrestees, the analyses of their urine specimens, police and court records of prior criminal behavior and experience with the criminal justice system, and records of each arrestee's current case, including court warrants, rearrests, failures to appear, and court dispositions. Demographic variables include age, education, vocational training, marital status, residence, and employment. Items relating to prior and current drug use and drug dependency are provided, along with results from urinalysis tests for opiates, cocaine, PCP, and methadone. The collection also contains arrest data for index crimes and subsequent court records pertaining to those arrests (number of court warrants issued, number of pretrial rearrests, types of rearrests, failure to appear in court, and court dispositions), and prior criminal records (number of times arrested and convicted for certain offenses).